Microstructure Evolution and Shear Property of Cu-In Transient Liquid Phase Sintering Joints - Jiang, Bang; Zhang, Qiaoxin; Shi, Lin; Zhu, Chundong; Chen, Zhiwen; Liu, Li; Shi, Yan (Frontiers in Materials, 2021)
Transient liquid phase sintering (TLPS) is a promising joining technology that can achieve high-temperature resisted solder joints at low temperature, showing excellent potential in power electronics. In this work, Cu/Cu-In/Cu solder joints were successfully prepared by TLPS process. The effects of bonding pressure and holding time on the microstructure and shear strength of Cu-In TLPS joints at 260 °C and 320 °C were studied. The results showed that as bonding pressure increased from 0.1 MPa to 0.6 MPa, the porosity decreased and shear strength increased significantly. No obvious change was found as bonding pressure continued to increase to 1 MPa. As holding time increased at 260 °C, Cu11In9 was formed and gradually transformed to Cu2In that can withstand elevated temperature. Meanwhile, the porosity decreased while shear strength increased. It was calculated that volume expansion (12.74%) occurred during the phase transition from Cu11In9 to Cu2In. When bonding temperature increased to 320 °C, only Cu2In was detected and then gradually transformed to Cu7In3 with the growing holding time. As holding time reached 120 min, their porosity increased and lead to weak shear strength due to volume shrinkage (15.43%) during the phase transition from Cu2In to Cu7In3.